Pemberdayaan Kelompok Tani melalui Sistem Informasi Pertanian Berbasis Android - Riri Narasati; Rudi Kurniawan; Fikri Firmansyah; Gilang Ramadhan (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Farmer group empowerment is one of the important strategies in increasing agricultural productivity and farmer welfare. This research aims to develop and implement an Android-based agricultural information system as a medium for empowering farmer groups in Nganjuk Regency. The system is designed to provide access to agricultural information in a fast, accurate, and relevant manner, including weather information, commodity prices, cultivation techniques, and consultation with agricultural extension workers. The research method used is descriptive qualitative research with a case study approach. The system development process refers to the Waterfall model which includes the stages of analysis, design, implementation, testing, and maintenance. The implementation results show that the use of an Android-based information system significantly increases farmer group involvement in agricultural activities, accelerates the decision-making process, and improves access to agricultural information resources. In addition, the system facilitates two-way communication between farmers and extension workers, which was previously constrained by time and location limitations. The conclusion of this research is that information technology, especially Android applications, has great potential in empowering farmer groups in a sustainable manner. It is hoped that this system can be adopted more widely by other regions as an information technology-based farmer empowerment solution.